2018
DOI: 10.18203/2394-6040.ijcmph20180267
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and obesity among higher secondary level students of Tulsipur Municipality, Nepal

Abstract: Background: The global epidemic of overweight/obesity – termed “globesity” is a major public health problem where rates of obesity have tripled in developing countries over the last 20 years. Factors like studying in private schools, consumption of unhealthy diet, insufficient physical activity and shortened night-time sleep duration are shown to be related with overweight and obesity. Hence, this study aims to assess the prevalence of overweight/obesity and the relationship of BMI with the socio-demographic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
2
2
0
Order By: Relevance
“…Piryani et al 8 found that overweight is nearly nine times common in those who watch television more than 2 hours. Similar finding was also seen in the study done by Regmi et al 12 Risk of overweight was three times higher in adolescent girls watching television more than 2 hours in a study in Sri Lanka and seven times more in another study in India. 11,24 Watching television could be a factor for increase overweight due to less physical activities.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Piryani et al 8 found that overweight is nearly nine times common in those who watch television more than 2 hours. Similar finding was also seen in the study done by Regmi et al 12 Risk of overweight was three times higher in adolescent girls watching television more than 2 hours in a study in Sri Lanka and seven times more in another study in India. 11,24 Watching television could be a factor for increase overweight due to less physical activities.…”
Section: Discussionsupporting
confidence: 89%
“…The study of Piryani et al 8 showed prevalence of overweight is twice in private school. Similar results of higher prevalence in private school were also found in the studies of Regmi et al, 12 Gupta et al, 13 Kaur et al, 14 and Maharjan et al 15 Prevalence of overweight in female students is nearly 3 times more than the male students. Similar studies done in other districts of Nepal also found high prevalence of overweight and obesity among female students (Acharya et al 16 in Kaski and Regmi et al 12 in Tulsipur Municipality); another study by Koirala et al 17 in childhood overweight in Lalitpur district showed overweight to be more prevalent in female child (30.9%).…”
Section: Discussionsupporting
confidence: 78%
“…[1][2]10 In our study, the prevalence of high abnormal BMI was found more in males than in females which is opposite to findings of other previous studies of similar settings. 8,[11][12][13][14] Other than finding the prevalence across sex, we also found proportions of high abnormal BMI of children…”
Section: Discussionmentioning
confidence: 97%
“…This may be due to rapid rate of urbanization in Nepal. According to WHO, the prevalence of overweight and obesity had nearly tripled between 1975 and 2016 and had reached over 340 million children and adolescents aged [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] were overweight or obese in 2016. Among them, 18% of girls and 19% of boys were overweight and 6% of girls and 8% of boys were obese [2].…”
Section: Introductionmentioning
confidence: 99%